Assessing teacher-related experiential avoidance: Factor structure and psychometric properties of the Teachers Acceptance and Action Questionnaire (TAAQ-PT). (10th December 2021) - Galhardo, Ana; Carvalho, Bruna; Massano-Cardoso, Ilda; Cunha, Marina
ABSTRACT: The Teachers Acceptance and Action Questionnaire (TAAQ) was designed to assess teachers' experiential avoidance (EA) related to their professional context. The current study aimed to adapt the TAAQ for European Portuguese (TAAQ-PT) and address its factor structure and psychometric characteristics. EA is defined as an emotion regulation process encompassing the unwillingness to stay in touch with negative private events and deliberate efforts to control them. EA has been pointed out as a transdiagnostic process associated with a wide range of psychological difficulties, playing a pivotal role in their development and maintenance (e.g., depression and anxiety). A sample of 304 Portuguese teachers completed the TAAQ-PT, the Depression Anxiety and Stress Scales-21 (DASS-21), the Utrecht Work Engagement Scale (UWES), and the Five Facet Mindfulness Questionnaire (FFMQ). The TAAQ-PT one-factor structure was tested through confirmatory factor analysis and revealed a good fit to the data and excellent internal consistency. The TAAQ-PT showed significant positive correlations with depression, anxiety and stress symptoms and negative correlations with mindfulness and work engagement. Overall, the TAAQ-PT revealed to be a short, valid and reliable measure of teachers' EA.